The Impact of Green Bonds on Firm Value and the Role of ESG: Revisiting the Stakeholder Value Maximization Theory - Brilliant Fani, Asad Arsya; Prijadi, Ruslan (Gadjah Mada International Journal of Business, 2025)
This study evaluates managers’ motivations in decision-making and whether they aim to maximize value or meet environmental and social pressures at the expense of value. The authors utilize green bonds as a treatment and measure changes in firm value data using Tobin’s Q, controlling for times and individual fixed effects and several company characteristics. This research documents the positive impact of issuing green bonds on a firm's value using the difference-in-differences (DD) method. Our findings are confirmed over the aggregate sample and most of the industry subsample, whereas we observed negative associations between green bonds and firm value only in the industrial subsample (comprising industrial and commercial services, industrial goods, and transportation). These findings align with the hypothesis of the stakeholder value maximizing theory. So, we suggest that, based on the data we analyzed about green bond issuances, companies choose to issue green bonds to increase their overall value.